Isokinetic moment curve abnormalities are associated with articular knee lesions - Iacono, Antonio Dello; Buksbaum, Chen; Padulo, Johnny; Hetsroni, Iftach; Ben-Sira, David; Ayalon, Moshe (Biology of Sport, 2018)
The aim of this study was to test whether lesions of the medial meniscus (MM) and of the anterior cruciate ligament (ACL) are associated with specific abnormalities of isokinetic moment curves (IMCs). Fifty-four young adults (20 active healthy people, and 34 patients with unilateral knee injuries) were assessed through knee extensor and flexor isokinetic tests at 60°/s. Qualitative IMC analysis was performed using a novel classification system which identified three distinct abnormal shapes. The chi-squared (χ 2 ) test was used to determine the inter-individual and intra-individual differences between the groups. Quantitative IMC inter-group comparisons were performed by a one-way analysis of variance (ANOVA). Knees with MM and ACL lesions were consistently associated with IMC shape irregularities (p<0.001) and with abnormal quantitative scores (p<0.001). More specifically, knees with isolated ACL lesions and knees with combined ACL and MM lesions presented similar distribution of knee extensor and flexor IMC irregularities, which was not present in knees with isolated MM lesions. A possible association between specific knee pathologies and IMC irregularities was identified (all p<0.05). In conclusion, different knee pathologies may be associated with different qualitative IMCs, which could be used as an additional presentation tool in clinical settings.